The impact of aid on growth revisited: do donor motives matter? - Christopher Kilby; Axel Dreher (Institute for the Study of Labor (IZA), 2009)
The typical identification strategy in aid effectiveness studies assumes donor motives do not influence the impact of aid on growth. We call this homogeneity assumption into question, first constructing a model in which donor motives matter and then testing the assumption empirically.
urn:nbn:de:101:1-20090513542
Keywords: F35; O40; 330; Aid; growth; politics; Internationale Wirtschaftshilfe; Entwicklungshilfe; Public Choice; Wirkungsanalyse; Wirtschaftswachstum; Schätzung; Welt; Entwicklungsländer